Religious dynamics under the impact of imperialism and colonialism : a sourcebook - Bentlage, Björn, 1979- (Numen Book Series, 2016)
This sourcebook offers rare insights into a formative period in the modern history of religions. Throughout the late 19th and the early 20th centuries, when commercial, political and cultural contacts intensified worldwide, politics and religions became ever more entangled. This volume offers a wide range of translated source texts from all over Asia, the Middle East, and Europe, thereby diminishing the difficulty of having to handle the plurality of involved languages and backgrounds. The ways in which the original authors, some prominent and others little known, thought about their own religion, its place in the world and its relation to other religions, allows for much needed insight into the shared and analogous challenges of an age dominated by imperialism and colonialism.